O papel da via NO-sGC-cGMP e dos canais para potássio no efeito vasorrelaxante do nitrato de ciclohexanol, um novo doador de óxido nítrico com atividades hipotensora e antihipertensiva em ratos. - Mendes Júnior, Leônidas das Graças (2016)
Nitric Oxide (NO) is a relevant component in physiological processes of cardiovascular system. Evidence suggests that NO plays a major role in regulating blood pressure and impaired NO bioactivity, which is an important component of hypertension. Pharmacological compounds that release NO could exert beneficial effects in arterial hypertension. We investigated whether cyclohexane nitrate (HEX) could act as a NO donor and its potential cardiovascular effects in rats. HEX increases NO levels (33.23 ± 2.28 vs. 10.66 0.62 a.u.; n = 25 and 22; respectively; p < 0,05) in vascular smooth muscle cells (VSMC); this effect was not abolished by prior treatment with L-NGNitroarginine (L-NNA, 100 μM), an endothelial nitric oxide synthase (eNOS) inhibitor. HEX induced vasorelaxation in mesenteric cranial artery from normotensive rats; and endothelium denuded arteries had bigger maximum effect (ME) than arteries with functional endothelium (ME = 100.4 ± 4.1% vs. 67.0 ± 2.8%; n = 7 and 10; respectively; p < 0.05). Vasorelaxant efficiency of HEX was diminished (ME= 44.9 ± 9.4%; n = 6) when endothelium denuded arteries were pretreated with the NO scavenger 2-phenyl4,4,5,5,-tetramethylimidazoline-1-oxyl 3-oxide (PTIO, 300 μM) as well as the soluble guanylyl cyclase inhibitor 1H-[1,2,4]oxadiazolo[4,3-a]quinoxalin-1-one (ODQ, 10 μM) (ME = 38.6 ± 9.7%; n = 6). Tetraethylammonium chloride (TEA, 3 mM), a non-specific potassium (K+) channel blocker decreased the vasorelaxant potency of HEX (pD2 = 5.11 ± 0.12 vs. 3.65 ± 0.17; n = 10 and 7; respectively; p < 0.05). In contrast, specific blocking of BKca by TEA (1 mM) or Kv by 4-Aminopyridine (4-AP; 1 mM) did not change the standard relaxing curve for HEX. Only KATP channel blocker glibenclamide (GLIB, 10 µM) induced reduction in potency (pD2 = 5.11 ± 0.12 vs. 4.38 ± 0.09; n = 10 and 7; p < 0.05). In mesenteric artery rings pre-incubation with HEX (10-3 mM) did not affect the concentration-response curve to HEX when compared to non-treated rings (107.5 ± 1.0 vs. 100.4 ± 4.1 %, n = 7 and 6, respectively). Intravenous administration of HEX (1; 5; 10; 20 mg/Kg) elicited hypotension in normotensive animals (−20 ± 6; −32 ± 5; −57 ± 9 e −76 ± 9 mmHg, n = 6) and in hypertensive rats (−9 ± 5; −12 ± 3; −15 ± 6 e −79 ± 10 mmHg, n = 6). Finally, 6 weeks after induction of renovascular hypertension, oral treatment with HEX (10 mg/Kg/day) for 7 days reduced blood pressure in hypertensive animals when compared to animals treated with saline (134 ± 6 vs.162 ± 5 mmHg, n = 6, respectively, p < 0.05). In conclusion, our data demonstrate that HEX is a NO donor able to produce vasorelaxation via NO-cGMP-PKG pathway and activation of KATP channels. HEX does not induce tolerance in mesenteric artery. Furthermore, HEX induces hypotension in normotensive and hypertensive rats as well as produces antihypertensive effect in renovascular hypertensive rats.